In vitro comparison of cone beam computed tomography with different voxel sizes for detection of simulated external root resorption - Neves, Frederico S.; Freitas, Deborah Q. de; Campos, Paulo S. F.; Almeida, Solange M. de; Haiter-Neto, Francisco (Journal of Oral Science, 2012)
The present study compared the efficacy of cone beam computed tomography using different voxel sizes in the diagnosis of simulated external root resorption. The presence or absence of simulated defects on buccal, mesial and distal root surfaces of 20 premolars was evaluated. The defects were small (0.26 mm in diameter and 0.08 mm deep), medium (0.62 mm in diameter and 0.19 mm deep) and large (1.05 mm in diameter and 0.24 mm deep), equally distributed on each root surface. Images were obtained using Classic i-CAT cone beam computed tomography with different voxel sizes: 0.12, 0.20, 0.25 and 0.30 mm. Five oral radiologists evaluated the images. Accuracy, sensitivity, specificity, positive and negative predictive values were determined. The sensitivity decreased and specificity increased as voxel size increased. Accuracy values were the highest for the smallest voxel size (0.12 mm). The results for voxel sizes 0.20 mm and 0.25 mm were similar. Positive and negative predictive values were similar in all protocols, except with 0.30 mm, in which they were the lowest. In conclusion, external root resorption was more easily diagnosed when a smaller voxel size was used. (J Oral Sci 54, 219-225, 2012)